Life cycle assessment of carbon capture and storage/utilization: From current state to future research directions and opportunities - Cruz, Tatiane Tobias da [UNESP]; Perrella Balestieri, José A. [UNESP]; de Toledo Silva, João M. [UNESP]; Vilanova, Mateus R.N. [UNESP]; Oliveira, Otávio J. [UNESP]; Ávila, Ivonete [UNESP] (Elsevier, 2021)
The need to reduce greenhouse gas emissions and tackle climate change has mobilized the whole world towards finding technologies and creating public policies aimed at a decarbonization of different sectors of the economy. Carbon capture and storage/utilization (CCS/CCU) technologies can ease the transition to renewable energy so as to meet the growing energy consumption demand estimated for the next 30 years. However, the environmental benefits gained by these emerging technologies must be critically evaluated, and the life cycle assessment (LCA) has been widely and successfully applied for such a purpose. Thereby, this paper provides an overview of the LCA of CCS/CCU technologies found in literature through a comprehensive bibliometric analysis of publications from 1995 through 2018 in order to highlight the current state and future challenges. The main authors, countries, institutions and research areas that apply LCA of CCS/CCU technologies have been identified through analyzing performance indicators using science mapping software tools. Analyzes have revealed that, driven by climate change mitigation targets, a widespread application of the LCA has addressed different CCS/CCU technologies focused not only on fossil energy generation (electricity and fuels), but also upon renewable energy and industrial processes (mainly in the production of cement and chemicals such as methanol). Scientific gaps have also been identified with the aim of promoting and guiding new studies on the matter at hand. These gaps demonstrate the need to collect primary data for different processes and technologies associated with CCS/CCU and conduct more thorough LCA studies and integrated assessments applied to CCS/CCU technologies. Therefore, the main contribution of this paper is to highlight their evolution and assist new studies on the LCA of CCU/CCS technologies by seeking improvement in this field of research.
Keywords: Bibliometric analysis; CCS; CCU; LCA; Research gaps